2019
DOI: 10.1002/jcla.23158
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of PIVKA‐II, AFP, AFP‐L3, CEA, and their combinations in primary and metastatic hepatocellular carcinoma

Abstract: Background: Early diagnosis decreases the mortality of hepatocellular carcinoma (HCC). We aimed to investigate the usefulness of PIVKA-II, AFP, AFP-L3, CEA, and their combinations in the diagnosis of primary and metastatic HCC. Methods: One hundred and twenty patients with primary HCC (PHC), 115 with metastatic HCC (MHC), 89 with chronic liver disease (CLD), and 116 healthy volunteers were included. The diagnostic values of each marker and their combinations for HCC diagnosis were represented by ROC curve anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
(29 reference statements)
2
23
0
1
Order By: Relevance
“…The problem with AFP as a biomarker for HCC is that in up to 40% of HCC patients, AFP levels are normal, especially in the early stage of the disease ( Qi et al, 2019 ). Addition to the fact that several patients with benign liver diseases, such as gastrointestinal cancer, chronic hepatitis and liver cirrhosis also have elevated serum AFP ( Tsuchiya et al, 2015 , Omata et al, 2010 ) found that a significant percentage of small HCCs < 3 cm do not secrete AFP to reach a diagnostic level.…”
Section: Discussionmentioning
confidence: 99%
“…The problem with AFP as a biomarker for HCC is that in up to 40% of HCC patients, AFP levels are normal, especially in the early stage of the disease ( Qi et al, 2019 ). Addition to the fact that several patients with benign liver diseases, such as gastrointestinal cancer, chronic hepatitis and liver cirrhosis also have elevated serum AFP ( Tsuchiya et al, 2015 , Omata et al, 2010 ) found that a significant percentage of small HCCs < 3 cm do not secrete AFP to reach a diagnostic level.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literature, serum levels of PIVKA-II>217 mAu/ml was an independent risk factor of early HCC recurrence (p = 0.0001) (114,115). Feng Gao et al reported that the cutoff value of PIVKA-II was 445 mAU/ml (RR=2.307, 95% CI: 1.132-4.703, P=0.021) (33). However, the association between low PIVKA-II levels and longer survival was weak (116).…”
Section: Prognostic Prediction In Hccmentioning
confidence: 97%
“…The remaining Glu residues are called des-gcarboxy prothrombin. PIVKA-II contains less than 10 Gla residues, resulting in a deficiency of thrombogen synthesis (33). Hemker et al first observed the biosynthesis of PIVKA-II indirectly in 1963 (34).…”
Section: Structure and Signaling Pathways Of Pivka-iimentioning
confidence: 99%
“…Early detection and more effective management of liver cancer is therefore Ivyspring International Publisher necessary. While some HCC prognostic biomarkers have been recommended, such as α-fetoprotein (AFP) [4] and PIVKA-II [5], HCC survival is still poor. Better understanding of the mechanisms of HCC development and progression, as well as the identification of novel prognostic biomarkers is needed.…”
Section: Introductionmentioning
confidence: 99%